Survival physiology and sex ratio of the Chinese white pine beetle Dendroctonus armandi (Coleoptera: Scolytinae) during host colonization and overwintering. Issue 1 (29th May 2019) - Dai, L.; Zheng, J.; Wang, Y.; Sun, Y.; Chen, H.
Abstract: The Chinese white pine beetle Dendroctonus armandi (Coleoptera: Scolytinae) typically displays bivoltinism at altitudes below 1700 m in the Qinling Mountains, China. The periods of host colonization and larval overwintering are two important phases in the life cycle of bark beetles, as it is during these periods that they have to contend with host plant defences and periods of intense cold, respectively. Although during different seasons, the females and males of Chinese white pine beetles show varying tolerances to host plant terpenoids, the sex ratio and survival physiology condition of the two beetle generations are unknown. We investigated the sex ratio of individuals, and also examined the body mass, energy stores, and detoxication enzymes of males and females in each of the two generations in order to determine the overall population stability of each generation. We identified a female-biased sex ratio among adults in both generations. Furthermore, patterns of body mass, energy stores, and detoxication enzymes were found to differ between the two sexes and two seasons. Compared with the males, the females have a larger body mass and higher amounts of stored lipids, which are assumed to be adaptations designed to overcome host resistance and facilitate subsequent oviposition.